Development of theoretical model for quadruple-pass erbium doped fiber amplifier - Mohammed, Mohammed AbdulJawad (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
Optical fiber communication is an active research area within the communication field. A lot of work has been done to overcome attenuation problems by using different Erbium-doped Fiber Amplifier (EDFA) configurations. Despite these achievements, there are still rooms for improvement. This dissertation presents a theoretical analysis of Quadruple Pass EDFA model. The theoretical model has been proposed for the QP-EDFA configuration which utilizes optical circulators and tunable band pass filters (TBF) with two levels pump scheme through a EDF length of 10 to 15 m in the first and the second stage. This analysis is carried using rate equations to cover broad input signal powers starting from -50 to 0 dBm with 10 to 220 mW pumping powers. A comparative analysis is conducted to compare results of the theoretical modeling and the published experimental results. The comparative analysis showed that the proposed theoretical model has similar results compared to the published experimental results. In addition, an improved configuration is also proposed which utilizes Chirped Fiber Bragg Grating (CFBG) instead of the TBF because of CFBG blocking more ASE than TBF and has a lesser insertion loss. The design parameters are optimized using the numerical modeling to maximize the performance of the EDFA. Finally, the improved configuration managed to produce a gain of 70 dB for -50 dBm signal power at 1550 nm input signal wavelength.